Telitacicept for systemic lupus erythematosus-associated peripheral neuropathy: a case report - Tan, Jinhui; Huang, Hai; Tan, Linghua; Li, Bo; Wu, Ximei; She, Ruonan; Luo, Junjia; Yang, Haitao; Zhang, Haoru (Frontiers in Immunology, 2026)
Peripheral neuropathy (PN) is a challenging manifestation of systemic lupus erythematosus (SLE) with limited evidence-based treatment guidelines. Current standard therapies, including glucocorticoids (GCs) and cyclophosphamide (CYC), are often effective but carry significant risks, such as gonadal toxicity with CYC, which is a major concern for young women. This case report describes the successful use of telitacicept, a novel dual inhibitor of B-lymphocyte stimulator (BLyS) and a proliferation-inducing ligand (APRIL), in a 37-year-old female with SLE-associated PN. The patient had a 17-year history of SLE and lupus nephritis, previously treated with high cumulative doses of CYC (13.2g), GCs, and mycophenolate mofetil (MMF). She developed PN in 2023, confirmed by electromyography showing axonal and demyelinating lesions. Due to her age and fertility concerns, subcutaneous telitacicept (160 mg/week) was added to her ongoing regimen of prednisone (10 mg/day) and MMF. Following telitacicept initiation, the patient’s neuropathic symptoms (numbness and hypoesthesia) completely resolved within months. Inflammatory markers (ESR, hs-CRP) and complement levels normalized, and proteinuria decreased. This clinical improvement allowed for a significant reduction in prednisone to 2.5 mg/day and MMF dosage. A follow-up electromyography eight months later showed no abnormalities. To our knowledge, this is the first report of telitacicept use for SLE-PN. It demonstrates that telitacicept can be a highly effective and steroid-sparing therapy, offering a safer alternative for patients where conventional immunosuppressants like CYC are contraindicated, particularly those of reproductive age. Future studies should explore parallels with immune checkpoint inhibitor (ICI)-related neuropathies.